A population-based study of the influence of socioeconomic status on prostate cancer diagnosis in Taiwan - Chi-Chen Wu; Ching-Heng Lin; Han-Sun Chiang; Ming-Je Tang (BMC, 2018)
Abstract Background Disparities in prostate cancer (PCa) outcomes and their links to socioeconomic status (SES) have been intensively studied. A relatively low incidence rate and a high proportion of late-stage diagnosis have been documented in studies of Asian populations. For the past 20 years, the trend in the growth of PCa cases in Taiwan was opposite to that of Western countries. However, there is a striking paucity of local studies on these important issues. To mitigate this gap in knowledge, we exploited two population databases to investigate the impact of SES on PCa incidence rate and stage at diagnosis. Particularly, we sought to explore the discriminating capabilities of various indexes of SES on two diagnostic outcome indicators. Method We conducted a population-based, follow-up, observational study. Data of study populations and newly diagnosed PCa cases between 2011 and 2013 were collected from the National Health Insurance Research Database and the Taiwan Cancer Registry. We retrieved 50-79 old male subjects who were classified as government employee, enterprise employee, or labor class. People with a diagnosis of any type of cancer before January 1, 2011, were excluded. The influences of four independent variables, i.e., age, beneficiary's insurance status, occupation and income, were analyzed. We used Cox proportional hazard models to calculate the hazard ratios of PCa and used logistic regression models to analyze the odds ratios (ORs) of late-stage PCa diagnosis. Results The low crude PCa incidence rate (112 per 100,000 person-years) and the high percentage of late-stage presentation (44%) were similar to those found in previous studies of old Asian men. Unsurprisingly, age was consistently revealed to be the most determinant factor in PCa diagnosis, while the insurance status of the beneficiaries showed no significant difference. Significant socioeconomic disparities in PCa diagnosis were demonstrated by occupation and income indexes, individually or in combination. However, occupation and income showed varied capabilities in discriminating disparities between different outcome indicators. Conclusion Our study supported the findings of extant works showing that advantaged populations have a higher PCa incidence rate and a lower percentage of late-stage diagnosis. The discriminating capabilities of health disparity by occupation and/or income were contingent on the choice of health outcome indicators. The relatively high percentage of late-stage presentation is a critical public health challenge, and a tailored coping strategy is urgently needed. For more effective health policy-making, local socioeconomic effects on the other outcome indicators of PCa, such as incidence to mortality ratio, warrant further investigation.